High Serum Advanced Glycation End Products Are Associated with Decreased Insulin Secretion in Patients with Type 2 Diabetes: A Brief Report. (12th June 2017) - Okura, Tsuyoshi; Ueta, Etsuko; Nakamura, Risa; Fujioka, Yohei; Sumi, Keisuke; Matsumoto, Kazuhisa; Shoji, Kyoko; Matsuzawa, Kazuhiko; Izawa, Shoichiro; Nomi, Yuri; Mihara, Hitomi; Otsuka, Yuzuru; et al.
Abstract : Objective . Advanced glycation end products (AGEs) are important in the pathophysiology of type 2 diabetes mellitus (T2DM). They directly cause insulin secretory defects in animal and cell culture models and may promote insulin resistance in nondiabetic subjects. We have developed a highly sensitive liquid chromatography-tandem mass spectrometry method for measuring AGEs in human serum. Here, we use this method to investigate the relationship between AGEs and insulin secretion and resistance in patients with T2DM. Methods . Our study involved 15 participants with T2DM not on medication and 20 nondiabetic healthy participants. We measured the AGE carboxyethyllysine (CEL), carboxymethyllysine (CML), and methyl-glyoxal-hydro-imidazolone (MG-H1). Plasma glucose and insulin were measured in these participants during a meal tolerance test, and the glucose disposal rate was measured during a euglycemic-hyperinsulinemic clamp. Results . CML and CEL levels were significantly higher in T2DM than non-DM participants. CML showed a significant negative correlation with insulin secretion, HOMA-%B, and a significant positive correlation with the insulin sensitivity index in T2DM participants. There was no correlation between any of the AGEs measured and glucose disposal rate. Conclusions . These results suggest that AGE might play a role in the development or prediction of insulin secretory defects in type 2 diabetes.